Design Ecosystems: Customising the Architectural Design Environment with Software Plug-ins - Davis, Daniel; Peters, Brady (Architectural design, 2013)
As a preface to this section dedicated to the rise of plug‐ins, Daniel Davis and Guest‐Editor Brady Peters describe the shift in architectural culture that has seen the adoption of scripting interfaces ‐ once the preserve of CAD specialists ‐ spread to designers using code to create geometry and find form. They explain how this defines an entirely new landscape in which ‘cathedrals’ (monolithic applications) are challenged by ‘bazaars’ (generative‐modelling editors) populated by animal‐named plug‐ins, where architects become the formulators rather than just the end users of programs.